Decadal changes in mean annual rainfall drive long‐term changes in bush‐encroached southern African savannas. (30th May 2016) - Shekede, Munyaradzi D.; Murwira, Amon; Masocha, Mhosisi; Zengeya, Fadzai M.
Abstract: Bush encroachment can have profound effects on the ability of savanna ecosystems to provide goods and services to society. It is therefore crucial to understand the key drivers of bush encroachment in savannas. In this study, we test whether decadal changes in mean annual rainfall significantly explain changes in the dominant patch size as well as the density of bush patches at six protected savanna sites located along a rainfall gradient in Zimbabwe. We first performed Maximal Overlap Discrete Wavelet transform within the intensity‐dominant scale theoretical framework on multi‐temporal aerial photographs and high spatial resolution satellite imagery to objectively detect changes in the dominant patch dimension as well as the intensity of bush cover over a 40‐year period at six test sites. We then pooled the data and performed regression analysis relating changes in dominant scale and intensity to decadal changes in mean annual rainfall in order to deduce a possible connection between dynamics of bush encroachment and rainfall variability. Our results indicate a significant nonlinear relationship between changes in the dominant scale and decadal changes in mean annual rainfall ( R 2  = 0.85, F 13  = 35.96, P  < 0.01). In contrast, the relationship between decadal changes in mean annual rainfall and changes in intensity was weak and not significant ( R 2  = 0.29, F13  = 2.69, P  = 0.106). These results imply the importance of annual rainfall in explaining long‐term changes in the dominant scale of woody patches. However, mechanisms other than rainfall probably explain changes in the intensity of bush cover, and this needs further investigation.